When Transaction-Level Wage Transparency Can Increase Consumer Preference - Lucas Stich; Christoph Ungemach; Christoph Fuchs; Martin Spann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Firms are usually reluctant to disclose information about the production costs of their goods and services; however, some firms have recently started to disclose cost information to consumers. This research examines the consequences of disclosing transaction-level wage information on consumer preferences. Six experiments, both in field and lab settings across multiple service domains, document that disclosing a service worker's compensation can increase consumer preference for that firm's service if the compensation is sufficiently high (i.e., perceived as fair by consumers). This greater preference for services provided in a fair-wage setting is driven by consumers' feelings of anticipated guilt and higher expectations concerning quality. Available social norms regarding fair compensation and the nature of the service worker (human vs. non- human) are both identified as important boundary conditions of the proposed process. This research offers a first step toward understanding the psychological and behavioral consequences of disclosing transaction-level wage information to consumers, thereby enabling managers to better identify when they should disclose wage information as part of their marketing strategy. This research also informs policy makers on how to encourage social preferences and consumer choices in order to promote fair outcomes for consumers, firms, and workers.
Keywords: 330; transaction-level wage transparency; social preferences; fairness; pricing; wage inequality